Weather Conditions of the Manufacturing Environment Adaptation of the Human Body to the External Environment (Eurasian Scientific Herald, 2022)
This article discusses the adaptation of the human body to the external environment of the industrial environment. Each of the weather factors, individually or in combination, has a significant impact on a person's ability to work and health. In production conditions, almost all-weather factors are affected at the same time